Understanding local fishermen’s preferences and willingness to accept compensation for commercial sea cucumber farming in the Jaffna lagoon, Sri Lanka - Sooriyakumar, K.; Sivashankar, S.; Balamauran, R.; Sarujan, S. (Applied Ecology and Environmental Research, 2025)
This study examines the willingness of local fishermen to accept compensation for establishing commercial sea cucumber farms in the Jaffna Lagoon, Sri Lanka. A choice experiment was used to assess preferences for key attributes, including the rearing area of sea cucumbers, breeding sites for fish and crustaceans, tourist facilities, mangroves, and cost. A total of 164 respondents were randomly selected, and a random logit parameter model was used to examine their preferences. The study found that local fishermen are willing to accept compensation for sea cucumber farming in the Jaffna Lagoon and are also willing to pay more for enhanced fish breeding sites, tourist facilities, and mangrove protection. The estimated annual mean willingness to accept (WTA) compensation for the establishment of commercial sea cucumber farms in the Jaffna Lagoon is LKR 1842.25. Additionally, their mean annual willingness to pay (WTP) for improvements in breeding sites, tourist infrastructure, and mangrove conservation is estimated at LKR 1622.48, LKR 1272.48, and LKR 700.48, respectively. Furthermore, fishermen’s choices regarding fish and crustacean breeding sites are influenced by education and income. These insights provide valuable guidance for policymakers to develop sustainable strategies for commercial sea cucumber farming in the Jaffna Lagoon.
Keywords: Choice experiment; Sea cucumber farms; Random parameter logit model; Willingness- to-accept; Willingness-to-pay